Sampling rate and aliasing on a virtual laboratory - Mihai Bogdan (Journal of Electrical and Electronics Engineering, 2009)
The sampling frequency determines thequality of the analog signal that is converted. Highersampling frequency achieves better conversion of theanalog signals. The minimum sampling frequencyrequired to represent the signal should at least be twicethe maximum frequency of the analog signal undertest (this is called the Nyquist rate). In the followingvirtual instrument, an example of sampling is shown.If the sampling frequency is equal or less then twicethe frequency of the input signal, a signal of lowerfrequency is generated from such a process (this iscalled aliasing).The goal of this paper is to teach students basicconcepts of sampling rate and aliasing, to becomefamiliar with this concepts.